The Effect of Computer-Assisted Phonics Games on Thai Kindergarten Students’ Listening Proficiency and English Phonics Achievement - Srimanothip, Rachanee; Orlando González (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
This study was aimed at comparing the Kindergarten 2 students’ listening proficiency and English Phonics achievement before and after using computer-assisted phonics games in English Phonics class at an international school in Bangkok during the academic year 2020-2021. This research followed a one group pre-test post-test pre-experimental research design. One conveniently chosen class of 13 Kindergarten 2 students participated in this 8-week study. An instructional intervention was implemented in English Phonics class two sessions per week and 40 minutes per session. Statistical data analysis indicated that the difference between participants’ listening proficiency before and after using computer-assisted phonics games in English Phonics class was significant, favoring the latter condition. Moreover, the participants’ listening proficiency improved from good before using computer-assisted phonics games, to excellent after using such games. It was also found that there was a significant difference in participants’ English Phonics achievement before and after using computer-assisted phonics games in English Phonics class, favoring the latter condition. Results from the data analysis also showed that Kindergarten 2 students’ English Phonics achievement improved from a recommendation for English Phonics class support before using computer-assisted phonics games, to an excellent achievement after using such games. Based on the research findings, recommendations for students, teachers, administrators, curriculum developers and future researchers are provided.